Some Essays on Toleration in Late Eighteenth Century England - Mullett, Charles F. (Church history, 1938)
The theory of toleration, often the child of indifference or of sectarian interest, is most difficult to analyse, whatever the issues. It may derive from indifference to the “rights” of conscience, while hiding behind an interested manner. The advocate frequently tolerates religious differences and hysterically cries “Crusade” against an economic heresy; or he shows charity toward one sect and simultaneously invokes the wrath of God and the power of Parliament against another which he considers in error. Often the plea proceeds from a minority whose very existence depends on toleration, but which on becoming a majority, demands conformity from others. Moreover, some men who have evoked a positive philosophy of toleration express only an intellectual interest. Yet whatever the basis— sectarian interest, intellectual sympathy, indifference, or a passionate love of freedom—toleration has always aroused sympathy and devotion.